Analisis Spasial Temporal Perubahan Penggunaan Lahan Permukiman - Esti Ganda Sari; La Ode Amaluddin; Tahir Tahir; Andrias Andrias (Jurnal Penelitian Pendidikan Geografi, 2025)
Land is widely used by humans to meet their living needs. One of them is that land is used as a place for human habitation. The research aims to determine the spatial temporal changes in residential land use in 2014-2023 and determine the causes of spatial temporal changes in residential land use in Konda District and Ranomeeto District. This research uses spatial analysis on Landsat 8 images. The results of the research are that land use in Konda District in 2014-2023 saw changes in non-built land where the forest area decreased by 862 ha. Changes in built-up land resulted in an increase in plantation area by 88.70 ha, rice fields by 200.00 ha and residential area by 1.00 ha. In Ranomeeto District, in 2014-2023, there was an increase in the use of non-built-up land, namely bushes, 1,917.49 ha. For built-up land, the increase occurred in the residential criteria of 629.06 ha. The factors causing land change in Konda District and Ranomeeto District are economic factors, demographic factors and location factors.